Congenital atresia of the left main coronary artery: management of a 5-year-old child in extremis. (22nd November 2020) - Schmiady, Martin; Kretschmar, Oliver; Prêtre, René; Dave, Hitendu
Abstract: Atresia of the left main coronary artery is a rare coronary anomaly. We describe the case of a 5-year-old child presenting in emergency in extremis. Clinical findings of haemodynamic collapse, malignant ventricular tachyarrhythmias and severe mitral regurgitation were indicative of a possible ischaemic aetiology. Surgical revascularization of the atretic left main coronary artery segment using an interposition autologous saphenous vein graft was successfully performed. Abstract : Coronary artery anomalies are a diverse group of congenital cardiac malformations.